A novel approach for the detection and identification of sulfur mustard using liquid chromatography–electrospray ionization–tandem mass spectrometry based on its selective oxidation to sulfur mustard monoxide with N‐iodosuccinimide. (13th April 2021) - Prihed, Hagit; Shifrovich, Avital; Shamai Yamin, Tamar; Madmon, Moran; Smolkin, Boris; Chen, Ravit; Blanca, Merav; Weissberg, Avi
Abstract: A new derivatization strategy for the detection and identification of sulfur mustard (HD) via liquid chromatography–electrospray ionization–tandem mass spectrometry (LC‐ESI‐MS/MS) is developed. The method incorporates selective oxidation of the sulfide group by the electrophilic iodine reagent N ‐iodosuccinimide (NIS) to produce sulfur mustard monoxide (HDSO). The derivatization reaction efficiencies were evaluated with acetonitrile extracts of soil, asphalt, cloth, Formica, and linoleum spiked with HD at concentrations of 50–5000 pg/ml and found to be similar to that with pure acetonitrile. The current derivatization approach is the first to preserve the identity of chloride groups and support HD regulation and evidentiary findings.